An attempt of road network and settlement generalization in the General Geographic Database using DynaGEN environment - Karsznia, Izabela (Geodesy and Cartography, 2008)
The attempts at formalization of cartographic knowledge and its implementation in computer-aided environment to achieve the most automated level of the process have been performed for over ten years. For the past couple of years, the research on generalization have been focused on some particular tasks such as: collecting cartographic knowledge aimed at identifying the principles regulating the generalization process; formalizing of generalization principles; developing generalization models; evaluating new cartographic algorithms and data structures supporting generalization processes (ex. Applying the Delauney triangulation in the process of shifting buildings). The predominant sort of elaborations, however, concerns the generalization of either maps or spatial databases on large scales. The reason of such a state of art is directly connected with a wide sort of practical solutions of such kind of data. Basic spatial databases on country levels have been kept exactly on the scales of 1: I O OOO, 1 :25 OOO and 1 :50 OOO - and hence the need for automated generalization. However, until now, there are neither general standards nor unified principles of small-scale maps generalization. Both complexity and specific character of generalization process in overview-scales, which in practice bases mostly on an author's experience and intuition as well as on the need for taking a map context into account, make the whole task very difficult and complex. The main purpose of the performed experiments was to establish possibilities and limitations of the automated generalization of small-scale spatial data. The problem was studied from the point of view of its formalization as well as further development of a knowledge base concerning small-scale spatial data generalization in commercial software DynaGEN by Intergraph. The scope of the studies covered carrying out two generalization experiments. The first one concerned the generalization of thematic layers - road network and settlement for the area of the Lower Silesia Province. The second one was applied to the generalization of the same thematic layers in the Lodz Province.
Keywords: Generalization of spatial data; General Geographic Database; DynaGEN environment